1985
DOI: 10.1152/ajpheart.1985.248.5.h674
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic modulation of direct defibrillation energy in anesthetized dog heart

Abstract: Catecholamines facilitate ventricular defibrillation in animals. We examined the effects of beta-adrenergic stimulation and blockade on ventricular defibrillation threshold in anesthetized dogs. Calibrated shocks were delivered between epicardial and superior vena caval electrodes, and defibrillation threshold was measured before and after administration of isoproterenol and propranolol. Eight dogs (group 1) received isoproterenol before propranolol. Nine dogs (group 2) received propranolol before isoprotereno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…1) On the contrary, isoproterenol significantly increased the energy requirement for defibrillation in another study, 4) and it was also reported to have little influence on DFT. 6) In humans, the effect of epinephrine on the efficacy of internal defibrillation has been studied by Sousa, et al 7) Shocks that successfully terminated VF in the baseline state failed to achieve defibrillation during epinephrine infusion in 4 out of 16 patients.…”
Section: Earlier Studies On the Autonomic Modulation Of Electrical Dementioning
confidence: 98%
See 1 more Smart Citation
“…1) On the contrary, isoproterenol significantly increased the energy requirement for defibrillation in another study, 4) and it was also reported to have little influence on DFT. 6) In humans, the effect of epinephrine on the efficacy of internal defibrillation has been studied by Sousa, et al 7) Shocks that successfully terminated VF in the baseline state failed to achieve defibrillation during epinephrine infusion in 4 out of 16 patients.…”
Section: Earlier Studies On the Autonomic Modulation Of Electrical Dementioning
confidence: 98%
“…[1][2][3][4][5][6][7] Among these studies, Morillo, et al demonstrated a decrease in the defibrillation threshold (DFT) during treatment with muscarinic drugs. 5) Recently, intermittent electrical stimulation of the cervical vagus nerve by an implanted stimulator has been used to treat medically intractable epilepsy.…”
mentioning
confidence: 99%
“…Os efeitos dos betabloqueadores sobre a desfibrilação ventricular parecem ser variáveis, de acordo com o tipo de droga utilizada. O propranolol foi responsável por elevação de limiares em dois estudos 19,20 . Os autores atribuíram este efeito mais à sua ação estabilizadora de membrana do que à sua atividade bloqueadora betadrenérgica.…”
Section: Drogas Antiarrítmicas E Limiares De Desfibrilaçãounclassified
“…The present study's objective was to document whether acutely elevated pulmonary capillary wedge pressures (PCWPs) significantly affect the DFT in the setting of impaired left ventricular function. In particular, the DFT was determined and compared at baseline, with both mildly elevated PCWP (12)(13)(14)(15)(16)(17)(18)(19), and with grossly elevated PCWP (> 19 mmHg) in a canine model of acute volume overload with moderate left ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%